Clonally expanded human airway smooth muscle cells exhibit morphological and functional heterogeneity - Singh, Shailendra R.; Billington, Charlotte K.; Sayers, Ian; Hall, Ian P. (BioMed Central, 2014)
Background: Mesenchyme-derived airway cell populations including airway smooth muscle (ASM) cells, fibroblasts and myofibroblasts play key roles in the pathogenesis of airway inflammation and remodeling. Phenotypic and functional characterisation of these cell populations are confounded by their heterogeneity in vitro. It is unclear which mechanisms underlie the creation of these different sub-populations. The study objectives were to investigate whether ASM cells are capable of clonal expansion and if so (i) what proportion possess this capability and (ii) do clonal populations exhibit variation in terms of morphology, phenotype, proliferation rates and pro-relaxant or pro-contractile signaling pathways.